Cost‐effectiveness of sodium‐glucose cotransporter‐2 inhibitors versus dipeptidyl peptidase‐4 inhibitors among patients with type 2 diabetes with and without established cardiovascular diseases: A model‐based simulation analysis using 10‐year real‐world data and targeted literature review. Issue 7 (26th April 2022) - Peng, Zi‐Yang; Yang, Chun‐Ting; Ou, Huang‐Tz; Kuo, Shihchen
Abstract: Aim: We conducted a model‐based economic analysis of sodium‐glucose cotransporter‐2 inhibitors (SGLT2is) versus dipeptidyl peptidase‐4 inhibitors (DPP4is) in patients with type 2 diabetes (T2D), with and without established cardiovascular diseases (CVDs), using 10‐year real‐world data. Materials and Methods: A Markov model was utilized to estimate healthcare costs and quality‐adjusted life‐years (QALYs) over a 10‐year simulation time horizon from a healthcare sector perspective, with both costs and QALYs discounted at 3% annually. Model inputs were derived from analyses of Taiwan's National Health Insurance Research Database or published studies of Taiwanese populations. The primary outcome measure was the incremental cost‐effectiveness ratios (ICERs). Incorporated with our study findings, a targeted literature review was conducted to synthesize updated evidence on the cost‐effectiveness of SGLT2is versus DPP4is. Results: Over 10 years, use of SGLT2is versus DPP4is yielded ICERs of 3244 and 4186 per QALY gained for patients with T2D, with and without established CVDs, respectively. Results were robust across a series of sensitivity and scenario analyses, showing ICERs between ‐1074 (cost‐saving) and 8467 per QALY gained for patients with T2D with established CVDs and between 369 and 37 122 per QALY gained for patients with T2D without established CVDs. Conclusions: Use of SGLT2is versus DPP4is was highly cost‐effective for patients with T2D regardless of their CVD history in real‐world clinical practice. Our results extend current evidence by showing SGLT2is as an economically rational alternative over DPP4is for T2D treatment in routine care. Future research is warranted to explore the heterogeneous economic benefits of SGLT2is given diverse patient characteristics in clinical settings.